2013
DOI: 10.1152/ajpheart.00298.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of rapid vasodilation after a brief contraction in human skeletal muscle

Abstract: Crecelius AR, Kirby BS, Luckasen GJ, Larson DG, Dinenno FA. Mechanisms of rapid vasodilation after a brief contraction in human skeletal muscle. Am J Physiol Heart Circ Physiol 305: H29-H40, 2013. First published May 3, 2013 doi:10.1152/ajpheart.00298.2013.-A monophasic increase in skeletal muscle blood flow is observed after a brief single forearm contraction in humans, yet the underlying vascular signaling pathways remain largely undetermined. Evidence from experimental animals indicates an obligatory role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 69 publications
6
97
0
Order By: Relevance
“…Regardless of the initiating event, the relaxation of vascular smooth muscle in the resistance vessels appears to be due in part to activation of inwardly rectifying potassium channels (K IR ) (9). The results of most (8,11,27,32) but not all (10, 23) studies have found that endothelium signaling pathways make little or no contribution to peak reactive hyperemia in humans. In isolated vessels, endothelium removal or inhibition of nitric oxide synthase partially blocked both peak reactive dilation and the duration of dilation (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the initiating event, the relaxation of vascular smooth muscle in the resistance vessels appears to be due in part to activation of inwardly rectifying potassium channels (K IR ) (9). The results of most (8,11,27,32) but not all (10, 23) studies have found that endothelium signaling pathways make little or no contribution to peak reactive hyperemia in humans. In isolated vessels, endothelium removal or inhibition of nitric oxide synthase partially blocked both peak reactive dilation and the duration of dilation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, experiments measuring blood flow to the canine hindlimbs (14,15) indicate that vasodilation is necessary for the immediate hyperemia at the onset of muscle contraction. Studies published over the last decade have provided evidence for the involvement of adenosine (2), potassium (8,9), and vascular compression (6,16,37) in rapid vasodilation of the skeletal muscle resistance vasculature.…”
mentioning
confidence: 99%
“…Armstrong et al (11) originally demonstrated that the initial vasodilation in the hamster cremaster muscle in response to muscle contractions was attenuated when 1) release of K ϩ from voltage-dependent K ϩ channels in skeletal muscle were inhibited, 2) inwardly rectifying K ϩ (K IR ) channels in smooth muscle were blocked, or 3) Na ϩ -K ϩ pump in smooth muscle was inhibited. More recently, inhibition of K ϩ -mediated vascular hyperpolarization in the human forearm effectively attenuates the peak and total vasodilator response to various intensities of single muscle contractions (107).…”
Section: Rapid Chemical Vasodilationmentioning
confidence: 99%
“…Emerging evidence in young humans also suggests a potential role of NO in contraction-induced rapid vasodilation (54,85,107). NOS inhibition alone (85), in combination with muscarinic receptor blockade (54), or cyclooxygenase inhibition (107) significantly reduces the peak and total postcontraction vasodilation.…”
Section: Rapid Chemical Vasodilationmentioning
confidence: 99%
“…In contrast, vasodilation occurs near-instantaneously with single brief contractions in rodents (23, 34, 51), as well as humans (9 -11, 48). While several mechanisms have been proposed to initiate ROV (10,48,51), as well the inhibition of ROV through ␣AR activation (5,23), no studies have investigated whether there may be a role for Cav2 in this regard. A key finding here is that loss of Cav2 depressed ROV by approximately half throughout the resistance network (Fig.…”
Section: Functional Vasodilationmentioning
confidence: 99%